EFEKTIFITAS GABUNGAN TES SUBJEKTIF DAN TES OBJEKTIF DALAM MENGEVALUSI HASIL BELAJAR FISIKA SISWA SMP NEGERI 11 BANDA ACEH - Pinte Rejeki (FKIP Unsyiah, 2016)
The study, titled Effectiveness of Combined Test of Subjective and Objective Tests in Evaluating Learning Physics Students SMPN 11 Banda Aceh. The problem is the low result of learning physics student who was suspected due to the incomplete evaluation system used by teachers, both subjective and objective. This study aims to determine the effectiveness of a combination of subjective and objective tests test in evaluating student learning outcomes physics. The study population was the eighth grade students of SMP Negeri 11 Banda Aceh the school year 2015/2016, amounting to 46 students. And the number of the sampled population numbered 20 students. The samples were done at random (random sampling). The method used qualitative method with descriptive approach. The data collection was done by using the test and data processing using a percentage (the results achieved each student is calculated from the percentage of correct answers). The results of data analysis showed that the percentage menunggunakan combined effectiveness tests are subjective and objective tests to evaluate student learning outcomes physics SMPN 11 Banda Aceh. Based on the category of the reference value of this research, the average value of above 60% are in the good category. Thus, the ability of the average eighth grade students of SMP Negeri 11 Banda Aceh the school year 2015/2016 in combination of subjective and objective test based on the research results is quite good.Keywords: effectiveness, subjective tests, objective tests, the combined objective tests and objective test, evaluation, learning outcomes. Penelitian yang berjudul Efektivitas Gabungan Tes Subjektif dan Tes Objektif dalam Mengevaluasi Hasil Belajar Fisika Siswa SMP Negeri 11 Banda Aceh. Masalahnya adalah rendahnya hasil belajar fisika siswa yang diduga akibat belum sempurnanya sistem evaluasi yang digunakan guru, baik yang subjektif maupun objektif. Penelitian ini bertujuan untuk mengetahui efektifitas gabungan tes subjektif dan tes objektif dalam mengevaluasi hasil belajar fisika siswa. Populasi penelitian ini adalah siswa kelas VIII SMP Negeri 11 Banda Aceh tahun pelajaran 2015/2016 yang berjumlah 46 siswa. Dan jumlah populasi tersebut dijadikan sampel berjumlah 20 siswa. Penentuan sampel dilakukan secara random (random sampling). Metode yang digunakan metode kualitatif dengan pendekatan deskriftif. Pengumpulan data dilakukan dengan teknik tes dan pengolahan data menggunakan persentase (hasil yang dicapai setiap siswa dihitung dari persentase jawaban yang benar). Hasil analisis data menunggunakan persentase menunjukkan bahwa terdapat efektivitas gabungan tes subjektif dan tes objektif dalam mengevaluasi hasil belajar fisika siswa SMP Negeri 11 Banda Aceh. Berdasarkan kategori nilai yang menjadi acuan penelitian ini, nilai rata-rata diatas 60% berada pada katagori baik. Dengan demikian, kemampuan rata-rata siswa kelas VIII SMP Negeri 11 Banda Aceh tahun pelajaran 2015/2016 dalam gabungan tes subjektif dan objektif berdasarkan hasil penelitian ini tergolong baik.Kata Kunci: efektivitas, tes subjektif, tes objektif, gabungan tes subjektif dan tes objektif , evaluasi, hasil belajar.